2019
DOI: 10.1080/1540496x.2019.1570842
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exchange Rates on Chinese Trade: A Dual Margin Approach

Abstract: Previous studies investigating the effect of exchange rate changes on a country's exports have found little evidence that exchange rates matter. This "Exchange Rate Disconnect Puzzle" may stem from the fact that studies have mostly focused on aggregate data. We analyze the effect of real exchange rate fluctuations of the RMB by decomposing Chinese trade into its "extensive" and "intensive" margins using product-level data. Contrary to recent empirical evidence on the insignificant effects of exchange rate chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…The United States of America has criticized China's exchange rate policy for the two country's bilateral trade deficit [73][74][75]. Evidence indicates that exchange rate volatility harms exports both in the short-and-long run [8,76]. Thus, our result is supportive of prior studies.…”
Section: Plos Onesupporting
confidence: 85%
See 1 more Smart Citation
“…The United States of America has criticized China's exchange rate policy for the two country's bilateral trade deficit [73][74][75]. Evidence indicates that exchange rate volatility harms exports both in the short-and-long run [8,76]. Thus, our result is supportive of prior studies.…”
Section: Plos Onesupporting
confidence: 85%
“…China, being the world's second-largest economy, has a significant impact on global trade patterns and the global economy [4,5]. Since its transformation into the global fastest rising economy, China has made remarkable changes in its export structure [6][7][8]. China's structural changes began in 1978, when the country started its economic reform and opening-up program.…”
Section: Introductionmentioning
confidence: 99%
“…Using a panel of 25 years of quarterly data, Chit et al (2010) found that currency volatility had a detrimental effect on the exports of five emerging East Asian economies (China, Indonesia, Malaysia, Philippines, Thailand). Real exchange rate volatility has been proven to have a major impact on overall Chinese exports, operating at both the extensive and intensive margins of trade (Qiu et al, 2020).…”
Section: Literature Review and Contribution Of The Researchmentioning
confidence: 99%